Measuring Supplier Service Quality in Indian SMEs Using Factor Analysis & GTA - Surjit Kumar Gandhi; Anish Sachdeva; Ajay Gupta (Jurnal Teknik Industri, 2018)
This study uses a hybrid scale to identify the factors contributing to the services delivered by the suppliers working with SME units in Indian setting. Application of EFA, CFA followed by GTA brings out a numerical measure of service quality index. 120 executives working at top/middle management levels in different SMEs of northern India responded to a questionnaire survey related to the assessment of services being delivered by their suppliers. The executives evaluated performance of their suppliers on the 1-5 Likert scale. Application of EFA followed by CFA revealed an interpretable latent structure comprising of five factors viz., Credibility, Relationship, Understanding, Alignment, and Dependability with 17 indicator items. Further, application of GTA resulted in an index value of Supplier Service Quality. This paper thus provides a framework for the measurement of SSQ in a previously less explored manufacturing sector. The proposed scale can be used as a benchmark by SME units for evaluation of supplier service quality. This methodology used may be applied in more such situations so that generalizations can be contemplated.